Novel CineECG to identify disease onset and progression in pathogenic plakophilin-2 mutation carriers. (19th May 2022) - Boonstra, MJ; Kloosterman, M; Asselbergs, FW; Van Dam, PM; Loh, P
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Dutch Heart Foundation Introduction: Arrhythmogenic cardiomyopathy (ACM) is a heterogeneous progressive disease. Identification of patients at risk for malignant ventricular arrhythmias is challenging, making extensive cardiac follow-up necessary. CineECG provides insight in the average cardiac pathway of cardiac electrical activity. In previous studies, CineECG proved useful to detect disease progression. Objective: Evaluate the applicability of CineECG to monitor disease progression in plakophilin-2 (PKP2) pathogenic mutation carriers. Methods: To compute the CineECG, a 3D heart/torso model and 12 lead ECG is used. From 68 PKP2 pathogenic mutation carriers, all raw ECGs were extracted from the patient database. In pathogenic mutation carriers with definite ACM, the ECG ±2 years before (ECG1), at (ECG2) and ±2 years after (ECG3) diagnosis were selected. In pathogenic mutation carriers without definite ACM, the most recent ECG (ECG2) and the ECG ±2 years before (ECG1) were selected. CineECGs were computed for the QRS complex and the distance between CineECG location at end QRS was determined per subject for subsequent CineECGs. Results: In 53 pathogenic mutation carriers ≥2 ECGs were available. 33 pathogenic mutation carriers were diagnosed with definite ACM of whom 4 had an ECG before, at and after diagnosis. Average distance between CineECG location at end QRS was 7.8±6.8 mm. In pathogenic mutation carriers with definite ACM, CineECG before and at diagnosis (figure, example 1&2) were different whereas CineECG at and after diagnosis did not always change. In pathogenic mutation carriers without definite ACM, in 14/19 changes in CineECG were observed (figure, example 3), whereas in the others (figure, example 4) not. Conclusion: Our preliminary results show that CineECG provides additional insight in the changes of cardiac activation in ACM patients and may enable detection of disease progression. Further analysis will also include cardiac repolarization.